THE CONCEPT OF THE SOIL BIOGEOSYSTEM - Smyrnova, S.; Smyrnov, V.; Babushkina, R. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The conceptual bases of the functional capacity of the soil biogeosystem (SB) are investigated, on which its composition and structure largely depend. Modern approach to understanding the complexity of the processes implemented in the soil cover should be based on the principle of polyfunctionality. The soil cover (in the sense of its length within the biosphere) is located at the intersection of the migration paths of the lithosphere, atmosphere, hydrosphere and biosphere as a whole, which determines its specific role in the complex system of geospheres and its polyfunctionality. Soil heterogeneity has been analyzed (solid, liquid, gaseous, living phases). Each phase is separately characterized, which has its own unique set of characteristics, formed in the process of evolutionary soil formation and is unique throughout the length of landscapes. Attention is focused on the diversity of the genetic nature of soils, which reflects their functional properties. The reflection of the genetic identity of soil, as a function of the environmental conditions of its formation, is the morphogenetic structure of the soil profile, which is formed in the process of soil formation. The principle of polyfunctionality of the soil geological system is defined, which describes the totality of processes at the global (biospheric) and biogeocenotic levels. On the one hand (from a global position), the SB determines the evolutionary orientation of biota on Earth, provides a large and small circulation of substances, regulates the chemical composition of the accompanying geospheres (atmosphere, hydrosphere), acts as a bioproductivity factor of terrestrial ecosystems and a battery of non-biogenic substance and energy depot, with the other (from the biogeocenotic position) SB is characterized by a number of physical, chemical, biochemical, and physicochemical functional properties. It has been established that the versatility of the processes that are implemented within the framework of the SB allows us to focus on the conceptual basis of a balanced anthropogenic load, and, consequently, on the preservation of biodiversity and humans as a biological species.
Keywords: soil cover; soil multifunctional; biogeocenotic functions of soil; soil heterogeneity; soil fertility; population-specific level; soil polyphase; biophase; migration; homeostasis